The value of critical destruction: Evaluating multispectral image processing methods for the analysis of primary historical texts. (6th October 2015) - Giacometti, Alejandro; Campagnolo, Alberto; MacDonald, Lindsay; Mahony, Simon; Robson, Stuart; Weyrich, Tim; Terras, Melissa; Gibson, Adam
Abstract: Multispectral imaging—a method for acquiring image data over a series of wavelengths across the light spectrum—is becoming a valuable tool within the cultural and heritage sector for the recovery and enhancement of information contained within primary historical texts. However, most applications of this technique, to date, have been bespoke: analysing particular documents of historic importance. There has been little prior work done on evaluating this technique in a structured fashion, to provide recommendations on how best to capture and process images when working with damaged and abraded textual material. This article introduces a new approach for evaluating the efficacy of image processing algorithms in recovering information from multispectral images of deteriorated primary historical texts. We present a series of experiments that deliberately degrade samples cut from a real historical document to provide a set of images acquired before and after damage. These images then allow us to compare, both objectively and quantitatively, the effectiveness of multispectral imaging and image processing for recovering information from damaged text. We develop a methodological framework for the continuing study of the techniques involved in the analysis and processing of multispectral images of primary historical texts, and a dataset which will be of use to others interested in advanced digitisation techniques within the cultural heritage sector.